Analisis Penggunaan Cat (Computer Assisted Test) Dalam Pemeriksaan Psikologi Guna Mendukung Efektifitas Proses Pelaksanaan Seleksi di Lingkungan Tni Angkatan Laut - Kurniasari, Afrida; Pakpahan, Faurna Lusiani; Marlina, Rina (Syntax Corporation, 2025)
This study aims to analyze the use of the Computer Assisted Test (CAT) in psychological assessments as a means to support the effectiveness of the selection process for prospective personnel in the Indonesian Navy (TNI AL). The background of this research stems from the challenges faced in selection implementation, which is still predominantly based on the conventional method (paper and pencil test), considered less efficient in terms of time, manpower, and result accuracy—especially in handling a large number of applicants distributed across various regions. This research employs a descriptive qualitative approach, utilizing in-depth interviews with psychologists from Dispsial, Dispsiau, and the Indonesian National Police, along with data analysis through NVivo 12 Plus software. The findings indicate that CAT offers several advantages, including time efficiency, improved objectivity and scoring accuracy, and better data security. However, the implementation of CAT within the Navy still encounters obstacles such as limited infrastructure, incompatible hardware, and a lack of technical training for system operators. Nevertheless, there remains significant potential for development, particularly through benchmarking against institutions that have successfully implemented CAT comprehensively. This study recommends enhancing infrastructure, developing a mobile and compatible CAT system, and strengthening policy and training for human resources involved. With the right strategies, CAT can serve as a strategic solution for modernizing the personnel selection system, making it more effective and accountable.